The effectiveness of the Elliott wave on Asian markets - Neo, Angeline Hui Mei (2009)
This paper focuses on the effectiveness of the application of the Elliott Wave theory on Asian Market Indices. The Wilcoxon Matched Pairs test was used to test for significant differences of profits between the Elliot Wave and the Moving Average Convergence Divergence (MACD), Stochastic Oscillators, Bollinger Bands and the Buy- Hold Strategy. Results have shown that the Elliot Wave is as effective as the other 3 indicators at producing returns. When transaction costs was considered, the Elliott Wave was most effective at producing significantly better profits than the 3 indicators and significantly lesser profits than Buy-Hold.